2019
DOI: 10.1111/trf.15552
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion of red blood cells does not impact progression‐free and overall survival after surgery for ovarian cancer

Abstract: BACKGROUND: Allogeneic red blood cells (RBCs) have the potential to impact the immunosurveillance of the recipient and may therefore increase the risk of recurrence after cancer surgery. In this article the relationship between perioperative RBC transfusion and the risk of recurrence after ovarian cancer surgery is examined.STUDY DESIGN AND METHODS: This is a retrospective cohort analysis of a prospective database of patients who underwent surgery due to primary ovarian cancer between 2006 and 2014 and who … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
0
8
1
Order By: Relevance
“…For instance, Connor et al demonstrated that PRBCT is associated with poor overall survival in advanced epithelial ovarian cancer patients [8]. While Hunsicker et al showed that perioperative transfusion of RBCs did not increase the risk of recurrence after ovarian cancer surgery [30]. Although, our results did not suggest a dose-response relationship between PRBCT Fig.…”
Section: Discussioncontrasting
confidence: 67%
“…For instance, Connor et al demonstrated that PRBCT is associated with poor overall survival in advanced epithelial ovarian cancer patients [8]. While Hunsicker et al showed that perioperative transfusion of RBCs did not increase the risk of recurrence after ovarian cancer surgery [30]. Although, our results did not suggest a dose-response relationship between PRBCT Fig.…”
Section: Discussioncontrasting
confidence: 67%
“…Additionally, rates of organ-space SSI, which are an imperfect marker and likely underestimate the incidence of anastomotic leak after bowel resection ( Rickles et al, 2013 ), were low overall, but were twice as likely to occur among patients who had bowel resection (1% vs 5%, p = 0.12). Recent studies have examined the impact of allogeneic red blood cell transfusion on recurrence and survival among patients undergoing surgery for ovarian cancer, with overall mixed results ( Zhang et al, 2020 , Hunsicker et al, 2019 , Pergialiotis et al, 2020 ). Given that our bowel resection cohort was much more likely to receive a blood transfusion (p < 0.01), consideration of this impact is warranted if transfusion of blood products is ultimately determined to be an independent predictor of worse recurrence and survival.…”
Section: Discussionmentioning
confidence: 99%
“…perioperative PRBC transfusion [8,[23][24][25][26]. The causes of these events are believed to be the immunosuppressive effect of PRBCs, due to the impaired function of NK cells and cytotoxic T lymphocytes [9]. However, the mechanisms responsible for the increased risk of cancer progression or recurrence after PRBC transfusions are not fully understood, as well as the involvement of bioactive mediators and blood components, capable of activating angiogenesis and survival pathways in transformed cells, is disputable [2,27].…”
Section: Plos Onementioning
confidence: 99%
“…An association between perioperative transfusion of allogeneic blood products and risk for recurrence has been shown in colorectal [3,6,7] and few other cancers [8], but the mechanisms of this phenomena have not been clarified yet. Due to the ambiguous literature reports and the small number of well-conducted randomized controlled trials, whether perioperative PRBC transfusion increases mortality and the risk of cancer recurrence in patients after surgical intervention is still debatable [9,10].…”
Section: Introductionmentioning
confidence: 99%